The Influence of the Clinical Nurse Leader Role on Healthcare Quality: A Narrative Review of Patient Outcomes, Care Coordination, and System-Level Efficacy - Alsadah, Hawraa Abdulhadi Haashim; almulhim, Nouf nasser abdulaziz; Alburayh, Zainab Abdullah; Alobud, Fatimah Yousef Abdullah; Alawad, Sawsan Hussain Mohammed; alzuwayyid, Rawan fahad abdultif; al marzooq, Rawan abdulrahman; Alruwaili, Asala Hamdan; ALALAWI, FATIMAH YASSEN ABDULLAH; ALNAZR, HASSAN ALI ABDULLAH (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Clinical Nurse Leader (CNL), initiated by the American Association of Colleges of Nursing in 2004, is a master-prepared role developed to enhance patient outcomes and microsystem-level care coordination in opposition to growing complexity in healthcare. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes evidence regarding the influence of the CNL on patient safety, quality, satisfaction, readmission, and care coordination, with challenges and future directions. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A Systematic review of various studies in PubMed, CINAHL, and Scopus was conducted, synthesizing quantitative and qualitative information. Two tables summarize CNL interventions and outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> CNLs reduced hospital-acquired infection (e.g., 20–40% reduction in CAUTIs), improved chronic disease management (5–10% reduction in HbA1c), enhanced patient satisfaction (10–15%), and reduced 30-day readmissions (10–25%). They enhanced interdisciplinary collaboration (15–20% improved communication) and optimized use of resources (10–15% shorter waits). Barriers are role ambiguity and uneven measures, for which there is sparse international evidence. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusions:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> CNLs have a substantial positive impact on patient outcomes and care coordination and align with healthcare reform objectives. Normalized measures, longitudinal data, and international studies are necessary to extend their influence, especially in underserved areas.